ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) DAN NET INTEREST MARGIN (NIM) TERHADAP RETURN ON ASSET (ROA) (studi Kasus Pada PT Bank Mandiri (Persero) Tbk Periode 2008-2012 - Irmawati, Irmawati; Sari, Dewi Kartika (Benefit: Jurnal Manajemen dan Bisnis, 2014)
This study aims to determine the impact of the Capital Adequacy Ratio ( CAR ) , Loan to Deposit Ratio ( LDR ) and Net Interest Margin ( NIM ) of the Return on Assets ( ROA ) at PT . Bank Mandiri ( Persero ) Tbk . The data used in this study comes from the banks concerned . The data taken in the form of secondary data obtained through the banking statistics quarterly financial report of PT . Bank Mandiri ( Persero ) Tbk in Indonesia during 2008-2012. The analytical method used consists of multiple regression analysis , the classical assumption , hypothesis testing ( t test and F test ) and test the coefficient of determination . From the results of this study concluded that based on regression analysis obtained the following equation : Y = 6.342 + 0.008 + 0.044 XI X2 - 1.176 X3 . In the classical assumption test found a problem in the autocorrelation test , whereas the normality test, multicollinearity and heteroscedasticity test there is a problem in the model .Â Based on the hypothesis testing , the F test is known that jointly ( simultaneously ) variable CAR , NIM and LDR significant effect on ROA . While the t test ( partial testing ) , variable CAR and NIM has no effect on ROA . While variable LDR dominant and significant positive effect on ROAÂ